2016
DOI: 10.1145/2937757
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Social Communication Skills Through Human-Agent Interaction

Abstract: There are a large number of computer-based systems that aim to train and improve social skills. However, most of these do not resemble the training regimens used by human instructors. In this paper, we propose a computer-based training system that follows the procedure of social skills training, a well-established method to decrease human anxiety and discomfort in social interaction, and acquire social skills. In this paper, we attempt to automate the process of social skills training by developing a dialogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…Based on our previous work [ 16 ], we related the following extracted features to speech and language: F0 variation, amplitude, voice quality, pauses, words per minute, words over six letters, and fillers.…”
Section: Basic Sst and Multimodal System Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous work [ 16 ], we related the following extracted features to speech and language: F0 variation, amplitude, voice quality, pauses, words per minute, words over six letters, and fillers.…”
Section: Basic Sst and Multimodal System Implementationmentioning
confidence: 99%
“…We previously developed a system called an automated social skills trainer that completely adheres to SST’s basic training model through an embodied conversational agent [ 16 ]. Based on extracted audio features, this system provides feedback for improving users’ social skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual agents are used for many different types of training programs, among which are social skills. For example the automated social skills trainer (ASST) [28], in which human-agent interaction takes place via user speech and language interaction. The proposed training focuses mostly on communication, previous research has been done in the same field, however no comparable virtual trainings are found.…”
Section: Social Skill Training With Virtual Agentsmentioning
confidence: 99%
“…interaction and communication. The smart class supports teachers' effective teaching and students' wellorganized communication (Tanaka et al, 2016). It uses the cloud service to make thinking collisions between the individuals which improve the abilities to communicate interindividually.…”
Section: Pedagogical Interaction Modelmentioning
confidence: 99%